Reading exercises in character analysis - Asor, Ester (Camacho) 1925- (s.n.], 1968)
The READING EXERCISES IN CHARACTER ANALYSIS is a seminar paper aimed at helping the high school student become a better reader by developing his insight and interpretative reading skills through an analysis of the characters presented in the reading exercises.